2021
DOI: 10.1038/s41598-021-92926-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel mumps virus epitopes reveal robust cytotoxic T cell responses after natural infection but not after vaccination

Abstract: Mumps is nowadays re-emerging despite vaccination. The contribution of T cell immunity to protection against mumps has not been clearly defined. Previously, we described a set of 41 peptides that were eluted from human leukocyte antigen (HLA) class I molecules of mumps virus (MuV)-infected cells. Here, we confirmed immunogenicity of five novel HLA-B*07:02- and HLA-A*01:01-restricted MuV T cell epitopes from this set of peptides. High frequencies of T cells against these five MuV epitopes could be detected ex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies focusing on the T-cell response against mumps have mostly investigated the response after MuV-vaccination, however it is generally observed that vaccination-acquired immunity is not as efficient as the long term response induced after a natural infection [16,34,296]. This is also the case for the T-cell responses to MuV-vaccination and MuV-infection.…”
Section: Longitudinal Characterization Of the Mumps-specific Hla-a2 R...mentioning
confidence: 99%
“…Studies focusing on the T-cell response against mumps have mostly investigated the response after MuV-vaccination, however it is generally observed that vaccination-acquired immunity is not as efficient as the long term response induced after a natural infection [16,34,296]. This is also the case for the T-cell responses to MuV-vaccination and MuV-infection.…”
Section: Longitudinal Characterization Of the Mumps-specific Hla-a2 R...mentioning
confidence: 99%